2015
DOI: 10.1088/1757-899x/101/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

ESS Accelerator Cryoplant Process Design

Abstract: Abstract. The European Spallation Source (ESS) is a neutron-scattering facility being built with extensive international collaboration in Lund, Sweden. The ESS accelerator will deliver protons with 5 MW of power to the target at 2.0 GeV, with a nominal current of 62.5 mA. The superconducting part of the accelerator is about 300 meters long and contains 43 cryomodules. The ESS accelerator cryoplant (ACCP) will provide the cooling for the cryomodules and the cryogenic distribution system that delivers the helium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The ACCP is the largest and most complicated of the ESS cryoplants. The cooling requirements and the initial concept design have been developed and improved over the years [107][108][109][110][111].…”
Section: Cryogenic Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ACCP is the largest and most complicated of the ESS cryoplants. The cooling requirements and the initial concept design have been developed and improved over the years [107][108][109][110][111].…”
Section: Cryogenic Systemsmentioning
confidence: 99%
“…The ACCP is the largest and most complicated of the ESS cryoplants. The cooling requirements and the initial concept design have been developed and improved over the years [107][108][109][110][111].Architecture.The ACCP consists of a warm compressor, oil handling and gas management station, located in the ACCP compressor building, and one single coldbox, located in the cold box building. The simplified block diagram in figure 60 shows the main components of the ACCP, consisting of:…”
mentioning
confidence: 99%
“…The CDS overall heat load at ~4K is dominated by the non-isothermal part in the VLP return circuit. According to [2] the ACCP has a specified heat load performance of 627W in our current configuration (with possibility to increase) and in [5] it is shown that the measured ACCP loads do even exceed this value. We have reasons to believe that the combined heat load of the CDS is adequate to support the SCL once the TAO have been removed.…”
Section: Static Heat Load Determinationmentioning
confidence: 95%
“…The expected electrical consumption for the 2 K nominal (Table 2) with the full warm compression solution is around 1.9 MW.  Hybrid compression using cold compressors in the refrigerator cold box and warm subatmospheric compressors ( [2] and [6]). The suction pressure of the warm sub-atmospheric compressors shall be adapted to the required turndown capability.…”
Section: The Sub-atmospheric Compressionmentioning
confidence: 99%